Vrijheid vandaag. - Theys, Hans; Van Meenen, Vincent (Aardenburg : Stichting Aardenburg Kunstenfestival, 2019)
AARS ; Janssens, Ann Veronica ; Dreisz, Annea Lyvv ; de Jong, Ate ; Lohaus, Bernd ; Claerbout, David ; De Klup ; Van Laethem, Dries ; Strik, Elly ; Van Coppenolle, Fran ; Milius, Gijs ; Mees, Guy ; Rombouts, Guy ; Visch, Henk ; Sevenans, Idris ; Baekelandt, Jolijn ; Dzobava, Jorik ; Philips, Karl ; De Vos, Kasper ; Van Accoleyen, Leon Frédéric ; Bal, Nicolas ; Baekelandt, Nienke ; Gielliet, Omer ; Peters, Oscar ; Blondbaard, Robby ; Soroko, Robert ; Ophuls, Max ; Masschelein, Simon ; Sterling, Ruby ; Van San, Tamara ; Troebel Neyntje ; Van Meenen, Vincent ; Swennen, Walter ; de Vos, Werner ; Van den Block, Zena ; Feigl, Zoro
Groepstentoonstelling 'Vrijheid vandaag!', diverse locaties in Aardenburg en Middelburg, 29.06.2019 - 18.08.2019.
Nederlands
boek